An Overview of the Application of Phasor Measurement Units (PMUs) and Network Coherent Data in an Interconnected Power Network: A Case for Namibia. Issue 2 (December 2017) - Gope, Gideon; Rens, Johan; John, Samuel
Abstract: This paper presents the technological background, the structure of a time-stamp for network coherent data and the emerging documentation on the data requirements for applications making use of network coherent data. Furthermore, the paper highlights relevant standards for synchrophasor measurements in power systems. The paper further mentions preliminary investigations on symmetrical component extraction in Namibia. The research potential of synchrophasor measurements and the concomitant potential value of Network Coherent Data for research purposes and power system operation and control have therefore not been extensively explored in the region. There is currently no evidence or example in Southern Africa (and in Africa) of the use of Wide Area Measurement Systems(WAMS) which make use of synchrophasors to support network operation and control.